Analysis of Audience Reception on the TikTok Account @meetnitelivemetrotv in Increasing Audience Interest in Consuming News : - - Bayquni BAYQUNI; Jatayu Hadi PRAKOSO (International Journal of Environmental, Sustainability and Social Science, 2025)
The rapid development of digital technology and social media has transformed the way audiences consume news, particularly among younger generations. TikTok, as a short-form video platform, has shifted from being merely a source of entertainment to becoming an important channel for information and news. This phenomenon raises a research problem regarding how audiences receive, interpret, and respond to news content presented in a new format, as exemplified by Metro TV’s official TikTok account, @meetnitelive. The purpose of this study is to analyze audience reception of the account’s news content and to explore how it influences public interest in consuming news. This research employs Stuart Hall’s Reception Analysis Theory, which emphasizes that audiences are not passive recipients of media messages but actively interpret them based on their social, cultural, and ideological contexts. Using a qualitative approach with a constructivist paradigm, the study finds that audiences occupy three interpretive positions: dominant, negotiated, and oppositional. The findings reveal that Metro TV, through @meetnitelive, successfully captures audience attention by delivering short, interactive, and visually engaging content aligned with digital trends. Nevertheless, some audiences remain critical of the accuracy, objectivity, and journalistic ethics of the news presented. These results underline that the success of media in the digital era depends not only on innovative formats but also on the ability to maintain credibility while fostering participatory audience engagement.